Use of functional respiratory imaging to characterize the effect of inhalation profile and particle size on lung deposition of inhaled corticosteroid/long-acting β2-agonists delivered via a pressurized metered-dose inhaler. (28th February 2018) - Van Holsbeke, Cedric; De Backer, Jan; Vos, Wim; Marshall, Jonathan
Background: Functional respiratory imaging (FRI) uses three-dimensional models of human lungs and computational fluid dynamics to simulate functional changes within airways and predict the deposition of inhaled drugs. This study used FRI to model the effects of different patient inhalation and drug formulation factors on lung deposition of an inhaled corticosteroid/long-acting β2 -agonist (ICS/LABA) combination, administered by a pressurized metered-dose inhaler. Methods: Three-dimensional models of the lungs of six patients with asthma (mean forced expiratory volume in 1 s, 83%), treated with an ICS/LABA, were included. FRI modelling was used to simulate (1) the effects on lung deposition of inhalation duration and particle size [fine particle fraction (FPF), proportion of particles <5 µm; and mass median aerodynamic diameter (MMAD), average size of inhalable particles]; (2) deposition of fluticasone propionate/formoterol (FP/FORM) 125/5 µg; and (3) how inhalation profiles and flow rates affected FP/FORM deposition. Results: Total lung depositions (TLDs) following 1-, 3- and 5-s inhalations were 22.8%, 36.1% and 41.6% (metered dose), respectively, and central-to-peripheral deposition (C:P) ratios were 1.81, 0.86 and 0.61, respectively. TLD increased with increasing FPF, from ~8% at 10% FPF to ~36% at 40% FPF (metered dose); by contrast, MMAD had little effect on TLD, which was similar across MMADs (1.5–4.5 µm) at each FPF. FP/FORM deposited throughout central and peripheral airways with gradual (sinusoidal) and sharp (rapid) inhalations. TLD ranged from 35.8 to 44.0% (metered dose) for gradual and sharp inhalations at 30 and 60 L/min mean flow rates. Conclusions: These data provide important insights into the potential effects of inhalation characteristics (inhalation profile and duration) and aerosol formulation (FPF) on lung deposition of inhaled therapies. FRI thus represents a useful alternative to scintigraphy techniques. Future FRI studies will further our understanding of the deposition of inhaled drugs and help improve the management of asthma.